Utilization of Tofu Rounder Machine in the Small Medium Entrepreneurship (SME) of Tofu Chips in Galang, Deli Serdang Regency, North Sumatra - Ridwansyah (Talenta Publisher Universitas Sumatera Utara, 2019)
The service team of the Food Science and Technology Study Program, Faculty of Agriculture along with the Community Service Institute of Universitas Sumatera Utara has conducted service activities for partner which are SMEs of tofu chips in the Hamlet II of Pisang Pala Village, Bangun Purba District, Deli Serdang Regency, North Sumatra Province between May and October in 2018. The partner named Roemah of Al Fatih, which produces raw tofu from soybeans, fried round tofu, and tofu chips. The main problem faced by the partner that began production in 2016 was the difficulty when making spherical of tofu dough as the starting material for tofu chips. So far, the partner has carried out the process of rounding out the dough manually using hand which took a long time. The service team offered a solution by granting a tofu rounder machine from stainless steel using electrical energy. Furthermore, the service team tested the production capacity of the tofu rounder machine and the conventional method (using hand). For the quality of round raw tofu (specific gravity and appearance of the product) and the quality of tofu chips, the team analysed and compared both products which were produced by hand and by machine. The results obtained the use of the tofu rounder machine can increase the capacity of round tofu production significantly, improve the appearance of round tofu products to be denser, and increase the value of preference for the texture of tofu chips produced. The grant of the tofu rounder machine is expected to help the partner for working up the company's profits in the future.